“Going hungry, walking, working, and being cold is hard”: Experiences of Venezuelan migrant parents and caregivers of minors - María Pineros-Leano; Beatriz Costas-Rodríguez; Megan M. Taylor; Nancy Jacquelyn Pérez-Flores; Diana Gomez; Natalia Piñeros-Leaño (PLoS ONE, 2025)
Background The Venezuelan crisis is one of the largest and most neglected migration crises in the Western hemisphere. Driven by economic, humanitarian, and human rights factors, nearly 8 million Venezuelans have migrated to other countries. Colombia hosts the largest group of Venezuelan migrants worldwide, with approximately 2.9 million Venezuelans residing there. Among these migrants are many Venezuelan parents and caregivers of minors who have resettled in different Colombian cities with their children. This descriptive qualitative study aims to identify their needs and highlight key opportunities for intervention. The perspectives of Venezuelan parents and caregivers of minors were complemented by those of service providers to identify systemic challenges and service gaps, providing a more comprehensive understanding of the population’s needs and priority areas for action. Using the Transnational Theory of Cultural Stress, this study explores the ways in which the experiences of Venezuelan migrant parents before, during, and after migration impact their current needs. Methods Using a combination of convenience and probability sampling, we collected semi-structured interviews from 29 Venezuelan parents and caregivers of minors residing in Colombia and 21 service providers who predominantly work with Venezuelan migrants. To analyze the data, we used thematic analysis. Results The analysis revealed three major themes: 1) lack of basic necessities forced Venezuelan families to migrate, 2) physical and emotional hardships experienced during the long migration journey, and 3) accumulation of ongoing challenges in Colombia left migrants feeling defeated. Conclusion The findings from this study underscore the importance of advancing the United Nations Sustainable Development Goals – including no poverty, reduced inequalities, and good health and well-being – in Venezuelan migrant families.